Smoothed maximum score estimation of discrete duration models - Sadat Reza; Paul Rilstone (Journal of Risk and Financial Management, 2019)
This paper extends Horowitz's smoothed maximum score estimator to discrete-time duration models. The estimator's consistency and asymptotic distribution are derived. Monte Carlo simulations using various data generating processes with varying error distributions and shapes of the hazard rate are conducted to examine the finite sample properties of the estimator. The bias-corrected estimator performs reasonably well for the models considered with moderately-sized samples.
Keywords: 330; maximum score estimator; discrete duration models; efficient semiparamteric estimation